FUNCTIONAL HYPOTHALAMIC AMENORRHEA - DIAGNOSTIC OVERLAP WITH PCOS AND ITS RELEVANCE IN THE FEMALE ATHLETE TRIAD: CURRENT CHALLENGES AND THERAPEUTIC STRATEGIES - Joanna Kaczor,; Zuzanna Wróbel,; Maja Torbacka,; Katarzyna Rozkosz,; Katarzyna Torbacka,; Aleksandra Sosin,; Natalia Wróbel,; Wojciech Bednarz,; Patrycja Podlejska,; Olga Jakubik, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Functional hypothalamic amenorrhea (FHA) accounts for a significant proportion of secondary amenorrhea and remains frequently overlooked, particularly in active women. Its clinical overlap with polycystic ovary syndrome (PCOS) complicates accurate diagnosis. In athletes, FHA arises primarily from low energy availability, forming a key component of the Female Athlete Triad. This review aims to summarize current evidence on the pathophysiology, diagnostic challenges, and therapeutic strategies for FHA, with emphasis on implications for women engaged in high levels of physical activity.Methods: A narrative literature review was conducted using the PubMed database, covering publications from 2012 to 2025. Search terms included amenorrhea, functional hypothalamic amenorrhea, polycystic ovary syndrome, and female athlete triad. Thirty-two relevant sources were included.Description of the State of Knowledge: FHA develops due to reduced pulsatile secretion of gonadotropin-releasing hormone (GnRH), resulting in suppressed LH and FSH release and impaired ovulation. Key contributing factors-energy deficit, excessive training, and psychological stress-disrupt neuroendocrine regulation and activate the hypothalamic-pituitary-adrenal axis. Recent studies highlight altered cortisol rhythms and changes in neurokinin B and nesfatin-1 as potential mechanisms. Differentiating FHA from PCOS remains a diagnostic challenge, particularly given the high prevalence of polycystic ovarian morphology in both conditions. Hormonal parameters such as SHBG, testosterone, and the LH:FSH ratio provide useful discrimination. Treatment focuses on restoring energy availability through nutritional rehabilitation and activity modification, supported by psychological interventions when indicated. For fertility restoration, pulsatile GnRH therapy offers a physiological approach, while IVF remains an effective alternative. Emerging options-including kisspeptin and L-carnitine-show promise in modulating neuroendocrine pathways.Conclusion: FHA is a prevalent yet underrecognized condition with substantial reproductive and skeletal consequences. Early identification and multidisciplinary management are essential to improving long-term health outcomes, particularly among physically active women.